NEGOSIASI ISLAM DAN BUDAYA: RITUAL BA’AYUN SEBAGAI MEDIA PEMBENTUKAN KARAKTER RELIGIUS DI KALIMANTAN SELATAN - Muhammad Syaifullah, Normuslim, Muslimah (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This article explores the dynamics of negotiation between Islamic values and local culture through the Ba’ayun ritual as a medium for building religious character within the Banjar community in South Kalimantan. Ba’ayun is not merely a life-transition ceremony for children, but a strategic instrument that harmoniously integrates Islamic teachings into local cultural practices. This research employs an interdisciplinary qualitative approach, combining sociological, educational, and anthropological perspectives to dissect the function of the ritual. The research findings indicate that Ba’ayun facilitates the internalization of character values through the stages of moral knowing, moral feeling, and moral action, which are supported by formal and informal pedagogical methods, such as the recitation of Quranic verses and exemplary behavior. Furthermore, this ritual serves as an instrument for social cohesion and a cultural buffer that strengthens communal identity amidst the currents of modernization. The legitimacy of the ritual within the framework of Islamic law is made possible through the role of local ulema who mediate religious texts with customs ('urf sahih). This article concludes that the successful negotiation between Islam and culture in the Ba’ayun ritual serves as a crucial foundation for national character building rooted in religious local wisdom.